PENGARUH MODEL PEMBELAJARAN MNEMONIC BERBANTUAN MEDIA GAMBAR TERHADAP HASIL BELAJAR IPAS PESERTA DIDIK KELAS IV - Dela Sefti Anggraini; Nurul Hidayah; Yuliyanti (Program Studi Pendididikan Guru Sekolah Dasar Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2025)
The learning process implemented by educators has varied in the use of learning models, but student learning outcomes are still relatively low. Based on these problems, this study applies a mnemonic learning model assisted by image media that has never been used before. This study aims to determine the effect of the mnemonic learning model assisted by image media on the learning outcomes of fourth-grade students in the subject of science at SD IT Maryam Muraith Martapura, East OKU Regency. The type of research used is quantitative with a quasi-experimental design (post-test only control design). The subjects of the study were fourth-grade students, consisting of an experimental class, a control class, and one validation class. The instrument used was a test, while the data analysis technique used a t-test. The results of the normality test showed a value of 0.113 and 0.397 > 0.05 so that the data was normally distributed. The homogeneity test produced a value of 0.245 > 0.05 which means the data was homogeneous. Hypothesis testing with an Independent Sample t-test showed a value of 0.000 < 0.05 so that H0 was rejected and Ha was accepted. Thus, there is a significant influence of the use of mnemonic learning models assisted by image media on student learning outcomes in the fourth grade science subject at SD IT Maryam Muraith Martapura, East OKU Regency.